DETEKSI BEGOMOVIRUS PADA TANAMAN CABAI MERAH DENGAN I-ELISA TEST DAN TEKNIK PCR - S. Mudmainah; Purwanto Purwanto (Universitas Tadulako, 2010)
The aim of this research was to study the symptom appear in the fields caused by Begomovirus or other viruses. The laboratory research was conducted using I-ELISA to comfirm the presence of Begomovirus and other mixed viruses and PCR to study coat protein band DNA of Begomovirus. The sample was collected from the plant that showed sympton of Begomovirus infection. The results of I-ELISA detection showed that the symptoms was varied in the field. The symptoms were mixed infection among Begomovirus and Tobamovirus, Cucumovirus, Potyvirus. Based on PCR detection, using universal primer coat protein of Begomovirus could amplify DNA fragment at 580 bp